Contos do cemitério: o protagonismo juvenil na literatura fantástica - Silva, Nilma Barros (2022)
The present academic work aims to present the youth protagonism in fantastic literature using as a basis the collection Contos do Cemitério (1997), produced by the French writer Yak Rivais. The series consists of six books: Sob o sol poente, sob o arco-íris, Na neblina, Ao vento de outono, Antes da tempestade e Depois da chuva. A set of three books were selected from the collection and from each work a short story was chosen for analysis in this academic work. The stories chosen were: ““Annick e a mão do diabo”, do livro Sob o sol poente; “O ogro de areia”, do livro Ao vento de outono; “Os defuntos se divertem”, do livro sob o arco-íris. As a foundation and ground basis of our study, we selected the concepts of Colomer (2003), Ceserani (2006) Todorov (1975), Camarani (2014), Roas (2014), Silva (2013), Rodrigues (1988), Vax (1963). Although the idea of a young group remains through the entire work, we opted for an individual analysis, in order to highlight the singularity of each character and how they relate to the fantastic elements of the texts. We hope with the development of this study to present two points worthy of greater prominence among Brazilian researches: the fantastic genre in children's literature and the aesthetic quality of Yak Rivais’ work.